2009
DOI: 10.1088/0004-637x/706/2/1451
|View full text |Cite
|
Sign up to set email alerts
|

Microlensing-Based Estimate of the Mass Fraction in Compact Objects in Lens Galaxies

Abstract: We estimate the fraction of mass that is composed of compact objects in gravitational lens galaxies. This study is based on microlensing measurements (obtained from the literature) of a sample of 29 quasar image pairs seen through 20 lens galaxies. We determine the baseline for no microlensing magnification between two images from the ratios of emission line fluxes. Relative to this baseline, the ratio between the continua of the two images gives the difference in microlensing magnification. The histogram of o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
210
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(221 citation statements)
references
References 52 publications
10
210
0
Order By: Relevance
“…In the mean time, there are a number of other interesting astrophysical probes in that mass range. These include future measurements of the stochastic gravitational-wave background [56][57][58][59][60] and of the mass spectrum [61], redshift distribution [62], and orbital eccentricies [63] for future binary-black-hole mergers; lensing of fast radio bursts by PBHs [64]; pulsar timing [65,66]; radio/x-ray sources [67] or the cosmic infrared background [68]; the dynamics of compact stellar systems [54]; strong-lensing systems [69]; and perhaps clustering of GW events [70][71][72][73]. The conclusions of our work suggest that it will be important to pursue vigorously these alternative avenues.…”
Section: Discussionmentioning
confidence: 99%
“…In the mean time, there are a number of other interesting astrophysical probes in that mass range. These include future measurements of the stochastic gravitational-wave background [56][57][58][59][60] and of the mass spectrum [61], redshift distribution [62], and orbital eccentricies [63] for future binary-black-hole mergers; lensing of fast radio bursts by PBHs [64]; pulsar timing [65,66]; radio/x-ray sources [67] or the cosmic infrared background [68]; the dynamics of compact stellar systems [54]; strong-lensing systems [69]; and perhaps clustering of GW events [70][71][72][73]. The conclusions of our work suggest that it will be important to pursue vigorously these alternative avenues.…”
Section: Discussionmentioning
confidence: 99%
“…Our results may also be used to derive the fraction of smooth matter in lensing galaxies. A study of the probability of deriving the observed values of μ in sample of lensed quasars, varying the fraction of compact/smooth dark matter along the line-of-sight of the lensed images, makes possible to constrain the fraction of matter in compact form in these galaxies (Schechter & Wambsganss 2004;Pooley et al 2009;Mediavilla et al 2009;Bate et al 2011;Pooley et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Mediavilla et al (2009) observed HE0435-1223 in the framework of a monitoring of 29 lensed quasars, and attributed eventual microlensing events to the normal stellar populations, while Blackburne & Kochanek (2010) focused on the quasar itself, applying a model with a time-variable accretion disk to the object. Mosquera et al (2011) found clear evidence of chromatic microlensing in the "A" component, and provided an estimate of the disk size in the R band in agreement with the simple thin-disk model.…”
Section: Introductionmentioning
confidence: 99%